A pilot study of hybrid biological activated carbon (BAC) filtration-ultrafiltration process for water supply in rural areas: role of BAC pretreatment in alleviating membrane fouling. Issue 2 (21st December 2017) - Qu, Fangshu; Yan, Zhongsen; Wang, Hao; Wang, Xiaobo; Liang, Heng; Yu, Huarong; He, Junguo; Li, Guibai
Abstract : For decentralized drinking water treatment in rural areas, a hybrid process of biological activated carbon (BAC) filtration and ultrafiltration (UF) was applied to obtain potable water. Abstract : For decentralized drinking water treatment in rural areas, a hybrid process of biological activated carbon (BAC) filtration and ultrafiltration (UF) was applied to obtain potable water. A pilot-scale study was performed by comparing BAC-UF and UF, and bench-scale experiments were also conducted to investigate the effect of BAC pretreatment on membrane fouling in UF. The performances of pilot scale BAC-UF and UF were continuously monitored for 130 days. BAC-UF performed better than UF in terms of dissolved organic matter (DOM) and ammonia removal. BAC pretreatment significantly alleviated membrane fouling in the subsequent UF. Besides reducing the organic loading that entered into the UF, BAC pretreatment also changed the quality of the DOM. BAC pretreatment shifted the major fluorescence foulants from fulvic and humic acid-like substances in the raw water to protein-like substances in the BAC effluent, and increased the apparent molecular weight of dissolved organics. Bench-scale UF tests showed that the BAC pretreatment reduced both reversible and irreversible fouling. Fouling mechanism analysis indicated that cake layer formation instead of pore blocking dominated fouling in UF with BAC pretreatment, which resulted in alleviated flux decline and higher stabilized flux. These results indicate that the changes in both the quantity and quality of DOM enabled by BAC pretreatment contributed to the retardation of flux decline and the increase in stabilized flux in BAF-UF.